A implantação do sistema de gestão da qualidade em uma cooperativa de planos de saúde de Araguaína-TO sob a ótica dos clientes. - Brito, Robson Sousa Brito (Universidade Federal do Tocantins, 2022)
The world economic scenario has undergone major changes driven by rapid technological evolution, increased customer requirements and cultural changes. With this, the search for satisfaction of their needs has become a matter of survival for companies in the face of an increasingly competitive economic scenario. Investments in the implementation of Quality Management Systems (QMS), previously seen as a differential, are now considered a necessity to achieve consumer satisfaction. The general objective of this study is to identify the result of the implementation of a QMS in a cooperative of health plans of Araguaína - TO. The methodology used for the production of this article consisted of a qualitative-quantitative evaluation based on a bibliographical and descriptive research. The studies show that achieving customer satisfaction is difficult because of the great diversity of requirements considered by each customer as a key satisfaction factor. In order to reach a quality service, the cooperative studied invested in the implementation of a QMS in order to change the culture and the company policy, aiming to meet the main requirements of its clients. After undergoing major changes aimed at enabling and raising awareness among professionals focused on meeting customer requests and complaints, the cooperative was able to achieve the latest ISO certification, and the benefits resulting from this project could be identified through the satisfaction survey of its clients. consumers.